ANTIFUNGAL STUDY AGAINST CURVULARIA SP. FROM UNCARIAGAMBIR ROXB LEAF EXTRACT: STUDI ANTIFUNGAL TERHADAP CURVULARIA SP. DARI EKSTRAKDAUN UNCARIA GAMBIR ROXB - Rexi Iswanto; Dodi Iskandar; Zaenal Mutaqin; Muliani; Danie Indra Yama (PT. ROCE WISDOM ACEH, 2025)
Isomitrafoline and Speciophylline show the strongest general Anesthetic (92.2) compared to other ligands. This study aims to determine the effect of gambir leaf extract on the growth of Curvularia sp. fungus and the concentration of extract that can inhibit 50% of the growth of fungal colonies. The research method used was a Completely Randomized Design (CRD) with 4 variations of extract concentration (0%, 5%, 10%, and 15%), each repeated 6 times. The results showed that the highest concentration of gambir leaf extract in inhibiting fungal growth was at a concentration of 15%. LC 50% analysis revealed that the concentration required to achieve 50% inhibition was 118.16%, indicating that the effectiveness of the extract against Curvularia sp. fungus is low or less toxic